Efforts to Create Relational Commitment Through Satisfaction Based on Company Image, Perception and Superior Service Quality (Study on Insurance Claiments PT. Jasa Raharja Perwakilan Semarang) - Rizal, Alimuddin; Mukti, Manggala Aji; Tjahjaningsih, Endang; Musthofa, Musthofa (Jurnal Manajemen, 2023)
This study is about efforts to build a relational commitment through satisfaction based on: corporate image, service quality and value perception. Respondents in the study were as Jasa Raharja Insurance Claimants at Semarang Reperesentative, amounting to 100 respondents. The sampling method uses purposive sampling. SPSS Version 19 data processing, data analysis techniques using regression. This study proposes seven hypotheses, after being tested by regression it is evident that there are four accepted hypotheses, namely the influence of company image, service quality, perceived value of satisfaction, and the effect of satisfaction on relational commitment. While the company's image hypothesis, service quality and value perspectives on relational commitment are not significant, meaning the three hypotheses are rejected. These results prove that the satisfaction variable is a variable that mediates the influence between company image, service quality and perceived value of relational commitment. However, the variables in this study have not been able to perfectly explain the phenomena that exist in building satisfaction and relational commitment. seen from the model test value (R2 Adjusted) in this study.